2012
DOI: 10.1038/ejhg.2012.254
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of Meckel–Gruber syndrome in Arabs reveals marked genetic heterogeneity and novel candidate genes

Abstract: Meckel-Gruber syndrome (MKS, OMIM #249000) is a multiple congenital malformation syndrome that represents the severe end of the ciliopathy phenotypic spectrum. Despite the relatively common occurrence of this syndrome among Arabs, little is known about its genetic architecture in this population. This is a series of 18 Arab families with MKS, who were evaluated clinically and studied using autozygome-guided mutation analysis and exome sequencing. We show that autozygome-guided candidate gene analysis identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…They identified diverse mutations in 10 different genes including 3 novel genes (C5orf42, EVC2, SEC8) . Shaheen et al's study [70] is the largest and most comprehensive genomic study of MKS in Arabs.…”
Section: Meckel Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…They identified diverse mutations in 10 different genes including 3 novel genes (C5orf42, EVC2, SEC8) . Shaheen et al's study [70] is the largest and most comprehensive genomic study of MKS in Arabs.…”
Section: Meckel Syndromementioning
confidence: 99%
“…MKS has also been reported in Saudi Arabia and Tunisia [68,69] . Shaheen et al [70] studied 18 Arab families with MKS using autozygome-guided mutation analysis and exome sequencing. Their study revealed genetic and allelic heterogeneity of this syndrome in Arab families.…”
Section: Meckel Syndromementioning
confidence: 99%
“…These processes may be dependent or independent on its fundamental role in exocytosis. Due to its role in many cellular processes, recent studies have suggested that the mammalian exocyst complex may be implicated in a number of diseases such as kidney disease (Charron et al, ; Fogelgren et al, ), ciliopathy (Fogelgren et al, ; Dixon‐Salazar et al, ; Shaheen et al, ), neuropathogenesis (Bolis et al, ), diabetes (Inoue et al, ; Chen et al, ), and cancers (Sakurai‐Yageta et al, ; Liu et al, ; Ashktorab et al, ; Tanaka et al, , ).…”
mentioning
confidence: 99%
“…6 Twelve genes are known to cause this disorder when in EVC2 and EXOC4 may also cause MKS. 7 In this study, we show that TMEM231 is the latest gene to be linked to MKS pathogenesis based on pathogenic mutations we identified in two families.…”
Section: Brief Reportmentioning
confidence: 68%